Gerenciamento de uma microrrede utilizando controle preditivo com incertezas meteorológicas - Silva, Danilo de Paula e (2020)
Microgrid management is a multi-objective problem that involves purchasing and selling energy, time-variant renewable generation, and maintenance costs. The microgrid can operate autonomously on an island or through mode connected with the main grid. This